2018
DOI: 10.1002/pros.23511
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cancer control outcomes in patients with biochemical recurrence and the impact of time from radical prostatectomy to biochemical recurrence

Abstract: Only a small proportion of BCR patients proceed to MP or PCSM. Besides higher GS and rapid PSA-DT a shorter RP-BCR interval (<12 months) heralds the most aggressive phenotype for progression to all three examined endpoints: MP, PCSM, and OM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…Time to BCR is also crucial for CRD as this has already been demonstrated in our multivariable analysis ( p = 0.03). Similar results are found in other studies (12, 13, 37). Briganti et al (13) appropriately point out correlation between early BCR and CRD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Time to BCR is also crucial for CRD as this has already been demonstrated in our multivariable analysis ( p = 0.03). Similar results are found in other studies (12, 13, 37). Briganti et al (13) appropriately point out correlation between early BCR and CRD.…”
Section: Discussionsupporting
confidence: 93%
“…It should be mentioned that Briganti et al defined early BCR as that which occurred in the first 3 years after RP. Pompe et al (37) demonstrated that CRD correlates with early BCR (≤1 year), pathological GS, and short PSA-DT. We did not calculate PSA-DT and pathological GS was not a significant factor for CRD in our study.…”
Section: Discussionmentioning
confidence: 99%
“…After primary curative-intent treatment for prostate cancer (PCa) with radical prostatectomy (RP) or radiotherapy, approximately one out of four men experience biochemical recurrence (BCR) (1).…”
Section: Introductionmentioning
confidence: 99%
“…(16) A limitation of the study was the lack of more definitive clinical endpoints such as death and although BCR is a clinically relevant determinate, it is largely considered a "surrogate" endpoint as only a small proportion of BCR patients will develop metastatic disease and/or die of prostate cancer. (2,17) Moreover, though that study did adjust for confounders through multivariable analysis, there was no further survival analysis of competing risks for BCR, such as death from another cause. We are unaware of any other studies which corroborate the work by Skove and we sought to validate these findings in an Australian population by querying the South Australian Prostate Cancer Clinical Outcomes Collaborative (SA-PCCOC) registry database.…”
Section: Introductionmentioning
confidence: 99%